VD_FINDINFO HC / 2019 / 60 vom 31. Januar 2019 - VD Tribunal cantonal (2019)
VICE DE FORME, LOYER ÉCHELONNÉ, ACTION EN CONTESTATION, RÉSERVE DE LA LOI, ABUS DE DROIT | 2 al. 2 CC, 253a al. 3 CO, 270d CO, 19 al. 2 OBLF